2022
DOI: 10.1111/1365-2435.14169
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic stress rather than biotic interactions drives contrasting trends in chemical richness and variation in alpine willows

Abstract: Plants produce an astonishing diversity of specialized metabolites as defences against herbivores, pathogens or detrimental abiotic conditions. Plants growing at different elevations are exposed to different biotic and abiotic conditions and typically show pronounced differences in their chemistry. Understanding how these differences arise through changes in various measures of chemical diversity can inform us concerning factors that contribute to the variety of metabolites found among plants. We focused on el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…Studying different Salix species along elevational gradients, Volf et al (2022) found an increase in the structural diversity (MPD) of salicinoids with altitude, but a decrease for flavonoids, which may result from variation in abiotic factors. Although evidence is limited so far, these studies suggest that structural diversity can be an important aspect of the phytochemical phenotype that varies with environmental conditions and affects function.…”
Section: Phytochemical Disparitymentioning
confidence: 99%
See 2 more Smart Citations
“…Studying different Salix species along elevational gradients, Volf et al (2022) found an increase in the structural diversity (MPD) of salicinoids with altitude, but a decrease for flavonoids, which may result from variation in abiotic factors. Although evidence is limited so far, these studies suggest that structural diversity can be an important aspect of the phytochemical phenotype that varies with environmental conditions and affects function.…”
Section: Phytochemical Disparitymentioning
confidence: 99%
“…Similar to results on evenness, Whitehead et al (2021) found that an increased structural diversity of phenolics, quantified as the mean pairwise dissimilarity (MPD) of all compounds in a mixture, increased the proportion of consumers negatively affected by the compounds. Studying different Salix species along elevational gradients, Volf et al (2022) found an increase in the structural diversity (MPD) of salicinoids with altitude, but a decrease for flavonoids, which may result from variation in abiotic factors. Although evidence is limited so far, these studies suggest that structural diversity can be an important aspect of the phytochemical phenotype that varies with environmental conditions and affects function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the 'lowland' species (Salix caprea, S. pentandra and S. purpurea) that typically occur in the colline and montane zones also include populations occurring in the subalpine zone. The intraspecific elevational variation in concentration or α-diversity of willow metabolites is typically smaller than interspecific differences and should not obscure the patterns explored here (Volf et al, 2022). Nonetheless, we limited our sampling of these three species to populations from the colline zone only.…”
Section: Field Samplingmentioning
confidence: 99%
“…They form diverse local assemblages and are broadly distributed from lowland floodplains to the alpine zone. Willow specialised metabolites mainly consist of phenolics with distinct functions, facilitating the comparison of trends in metabolites that play different roles in plant biology (Volf et al, 2015(Volf et al, , 2022. The phenolics found in willows include numerous flavonoids that are primarily involved in protecting willows against abiotic stress (Tegelberg & Julkunen-Tiitto, 2001).…”
Section: Introductionmentioning
confidence: 99%